THE IMAGE OF WOMEN IN THE NOVEL BELENGGU MERAH MUDA BY TYAS DAMARIA - Muhamad Zulzain; Irianto Ibrahim; La Ode Syukur (CASA CENDEKIA MEDIA, 2025)
The purpose of this study was to describe and analyze the image of women in the novel Belenggu Merah Muda by Tyas Damaria based on a feminist approach. This type of research is library research. The method used in this research is descriptive qualitative method. The data used in this research is written data contains the image of women seen from women's self-image, in the family, and education. The data source in this study is the novel Belenggu Merah Muda by Tyas Damaria which was published by Gramedia Pustaka Utama, Jakarta, in 2016 with 199 pages thick. The data collection technique used in this study was reading and note-taking. Data analysis used feminist analysis. The results of research on the novel Belenggu Merah Muda by Tyas Damaria are women's self-image and social image.